Thermal stresses in rectangular plates: variational and finite element solutions. - Laura, P. A. A.; Gutiérrez, R. H.; Sanchez Sarmiento, G.; Basombrio, F. G. (North Holland Publishing Co., 1978)
Fil: Laura, P. A. A. Comisión Nacional de Energía Atómica; Argentina